Membangun Jembatan Injil: Peran Pelayanan Sosial dalam Memfasilitasi Pemuridan dan Pertumbuhan Gereja - Nurlela Syafrian Oematan (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2025)
This study aims to analyze the role of social ministry in facilitating discipleship and church growth. Using a qualitative approach, the research was conducted at GMIT Kupang through interviews and observations. The findings reveal that social ministry builds relationships and paves the way for a more effective discipleship process. Theologically, social ministry represents a holistic expression of God's mission. The integration of evangelism, social action, and contextualized discipleship offers a relevant missional strategy for the contemporary church.